Seduction of far-right actions: A pathway to an authentic self? - Yoshida, Yutaka (Sage Publications, 2025)
Far-right civil movements have emerged as a significant predicament in numerous regions worldwide. Despite abundant research on the tactics employed by far-right groups to instil ideologies, behaviours and sentiments in their followers, such as street demonstrations, investigations into the meaningmaking of far-right actions in relation to the trajectories of the participants’ lives remain scarce. The present study uses the analytical tool proposed by Katz to explore how far-right activists obtain a sense of moral transcendence through their activism, including participating in the liminal moments of far-right rallies, revelling in unrestricted speech, discovering new abilities, acquiring knowledge and engaging in self-expression. We contend that these experiences engender in participants the sense that they are acquiring that which is absent from their lives and recovering their ‘true selves’. The study maintains that to comprehend the allure of the far right, it is essential to contextualise far-right actions within the participants’ lives, the societies that they inhabit, and the circumstances that surround them. In short, the sensation that one is rediscovering one’s ‘true self’ may encourage activists to pursue the more remote objective of reclaiming what they perceive as their nations’ lost ideals.